Factors Influencing Mental Health and Perceived Well-Being in Distance Learning Students: A Literature Review - Sri Yusriani; Shine Pintor Siolemba Patiro; Rifi Hamdani Sitohang; Muhammad Siddiq Idris Azzam (Greenation Publisher & Yayasan Global Research National, 2024)
Distance learning has become increasingly prevalent, but the mental health and perceived well-being of students in this mode of education require more attention. This literature review identifies key factors affecting mental health and well-being in distance learning students, including self-efficacy, social support, access to digital resources, and stress management. Examining high-impact studies from academic databases such as ScienceDirect, Sage Publications, and Emerald, the review aims to provide a comprehensive understanding of how these factors contribute to student well-being in remote learning environments. The findings emphasize the need for supportive interventions, such as digital literacy programs, mental health support, and accessible online resources, to mitigate the psychological challenges students face in distance learning.